A Case of Giant Bladder Carcinosarcoma without Submucosal Invasion. (5th May 2011) - Zaitsu, Masayoshi; Yamanoi, Mariko; Mikami, Koji; Tonooka, Akiko; Uekusa, Toshimasa; Takeuchi, Takumi
Abstract : Carcinosarcoma is a rare biphasic neoplasia containing both malignant mesenchymal and epithelial elements. Bladder carcinosarcoma commonly presented as high-grade, advanced stage, and aggressive behavior with a poor prognosis. An 83-year-old male presented with painless gross hematuria to our hospital. Cystoscopy revealed massive nonpapillary bladder tumor on the right wall. The 91 g tumor could be completely removed with transurethral resection. Histology of the tumor was diagnosed as carcinosarcoma with no submucosal invasion composed of biphasic malignant epithelial and mesenchymal cells. Epithelial malignancy was urothelial cancer and mesenchymal one was chondrosarcoma and leiomyosarcoma. The specimens taken at the second-look TUR-Bt revealed that carcinoma in situ (urothelial cancer) but not sarcoma existed at the mucosa surrounding the previous tumor site. 80 mg of BCG instillation intravesically every week for six weeks was successfully administered to the patient. There is no tumor recurrence for 6 months after treatments.